Spinal postural alignment measurements using markerless digital photography. (12th November 2020) - Hida, Mitsumasa; Wada, Chikamune; Imai, Ryota; Kitagawa, Kodai; Okamatsu, Shogo; Ohnishi, Tadasuke; Kawashima, Satoshi
Background: A device that can measure posture alignment repeatedly is important for the prevention of hyperkyphosis. Objective: We devised a markerless measurement method for hyperkyphosis using digital photography and investigated the correlation with other noninvasive measurements and the validity and accuracy of this method. Methods: The study included 27 participants. The craniovertebral angle in supine (CVAS) and craniohorizontal angle in supine (CHAS) were calculated from digital photographs of the head and neck areas of the studied subjects with ImageJ. The correlations of CVAS and CHAS with the kyphosis index (KI) and block method (BM) were investigated. Intrarater correlation coefficient and Bland–Altman analyses were used to verify the reliability and accuracy of the measured results. Results: CHAS exhibited an excellent correlation with the KI and the BM. The intra- and interrater reliabilities of CHAS were almost perfect. Bland–Altman analysis revealed that CHAS was associated with minor addition errors. Conclusion: CHAS founded an excellent correlation and reliability with the conventional spinal postural alignment measurements. The addition error suggested that the manual was needed to confirm the landmark. The CHAS is a method used to measure the spinal postural alignment in a supine position without markers and without exposing the skin surface.